Multifaceted role of Trichoderma harzianum isolates in mitigating drought stress and promoting adaptive responses in barley cultivars - Mona Sorahinobar; Nastaran Yusefieh; Maryam Rezayian; Samira Shahbazi (Scientific Reports)
Abstract This study investigated the effects of seed biopriming with two Trichoderma harzianum isolates, wild type (TW) and gamma-ray mutant (TM), on drought tolerance in the two barley cultivars, Goharan and Nosrat. Barley seeds primed with Trichoderma and subsequently exposed to drought stress induced by polyethylene glycol (PEG 6000) at concentrations of 0%, 5% and 10%. Drought stress significantly reduced growth (20–45% decrease in fresh and dry weight), with Nosrat showing a greater reduction than Goharan. Biopriming with TW and TM significantly improved plant growth (fresh and dry biomass by 4–56%), particularly with TM, and alleviated drought-induced oxidative stress (reduced H2O2 and MDA levels) by enhancing antioxidant defense systems (increased superoxide dismutase, peroxidase, and polyphenol oxidase activity) and non-enzymatic antioxidant content (total phenolics, flavonoids, and anthocyanins). TW and TM priming also improved osmotic regulation (increased protein and soluble sugars) and increased IAA content and the activity of key respiratory enzymes (aconitase, succinate dehydrogenase, malate dehydrogenase, and fumarase). These findings highlight the multifaceted role of biopriming with T. harzianum isolates in enhancing adaptive responses of barley to drought stress. Seed biopriming with TW and TM significantly improved barley cultivar resilience under drought conditions, suggesting their potential as effective drought tolerance strategies for crops.